A comparison of vertical jump displacements between a vertectm and a forceplate - Christensen, B.; Hilgers, S.; Schuna, J.; Radenic, C.; Krebsbach, K.; Terbizan, D.; Tucker, J.; Manikowske, T.; Liguori, G. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to compare vertical jump displacements between a VertecTM and a forceplate. Thirty-two Army Reserve Officers' Training Corps (ROTC) cadets completed three countermovement vertical jumps on a forceplate while simultaneously touching the highest vane they could reach on a VertecTM placed immediately next to the forceplate. The means between the methods were found to be significantly correlated (r=.91, p<.001). However, significant differences were found between the means (t=13.6, p<.001). With-in method analysis results showed no significant differences between the three jumps as estimated by the forceplate (F<.001, p=.985), however, significant differences were found between displacements as measured by the VertecTM (F=17.0, p<.001).